Brought to Light: Contemporary Freemasonry, Meaning, and Society, by J. Scott Kenney. (24th June 2018) - Weinbren, Daniel
Abstract : Brought to Light: Contemporary Freemasonry, Meaning, and Society, by J. Scott Kenney (Waterloo, Ontario, Wilfrid Laurier University Press, 2016), pp. xiv +294, £29.99, Pbk, ISBN 978-1-77112-194-1.